أسلوب المفتاح للعلوم في تحسين القدرة على قراءة الكتب التراث في معهد صالح الدين الإسلامي دامبيت مالانج - Djunaidi, Djunaidi; Sakdiyah, Choli Latus (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2023)
Islamic boarding schools are the oldest education system in Indonesia. One of the great traditions and characteristics of teaching in Islamic boarding schools is the yellow book (kutubut turost). The aim of this research is to describe the al-Miftah lil Ulum method and its effectiveness in improving the ability to read the turats. This research uses qualitative descriptive research. Data processing uses descriptive analysis techniques; observation, interviews, and documentation. The conclusion of the research shows that the process of implementing the Al-Miftah Lil 'Ulum Method at the Ash-Sholihuddin Islamic Boarding School is carried out through several stages, namely: preparation, implementation, and evaluation. Factors supporting professional Human Resources (HR), simple and easy material, adequate facilities and infrastructure, student perseverance in learning. The inhibiting factors do not totally influence the development of students' learning. And time constraints, environment (internal and external) and the inequality of the new school year. And the effectiveness of its use is very good for improving students' ability to read the turats.